The Influence of Interest in Reading PKN Lessonbook on the Student Learning Outcomes of SMP Nasional Palangka Raya - Isna Fauziah; Hendriyono LM; Sinta Sisilia (Budapest International Research and Critics University, 2022)
From the point of view of educators, teachers and schools must pay attention to materials or provide places and books for students so that they can be comfortable in increasing their knowledge about lessons by providing books and reading places such as libraries. This study was conducted to determine the effect of interest in reading Civics textbooks on student learning outcomes at the Palangka Raya National Junior High School for the 2019/2020 academic year. This research is an exposed facto research with a quantitative approach. The research sample was Palangka Raya National Junior High School students for the 2019/2020 academic year, consisting of 24 classes of VII, VIII and IX. Collecting data using questionnaires and documentation. The data analysis technique used is a simple regression test. The results showed that interest in reading books (X) on learning outcomes (Y) obtained the value oftcount = 3.076 with a probability value of 1.721. The probability value of t is less than the significant degree, which means that there is an influence of interest in reading Civics textbooks on the learning outcomes of Palangka Raya National Junior High School students for the 2019/2020 school year. Interest in reading books has an effect on increasing student learning outcomes. This is evidenced by the coefficient of determination of interest in reading books, which is 75.29% and 24.71% is influenced by other factors not examined in this study.